An Enhanced Slotted Binary Tree Algorithm with Intelligent Separation in RFID systems - SungSoo Kim; YongHwan Kim; KwangSeon Ahn (2009 IEEE Symposium on Computers and Communications, 2009)
In RFID systems, identifying the tag attached to the subject begins with the request from a reader. When the reader sends a request, multiple tags in the reader's interrogation zone simultaneously respond to it, resulting in collision. The reader needs the anti collision algorithm which can quickly identify all the tags in the interrogation zone. We propose the Enhanced Slotted Binary Tree Algorithm with Intelligent Separation (IS-ESBT). In IS-ESBT, a collision can be prevented because the tags which match with the prefix of the reader's request respond as followings; the group of tags with an even number of 1's in the bits to the prefix + 2 nd bits responds in slot 0, while the group of tags with an odd number of 1's responds in slot 1. The IS-ESBT generates the request prefix so that the only existing tags according to the response in the corresponding slot. That is, it decreases the tag identification time by reducing the overall number of requests.